2008
DOI: 10.1111/j.1467-8535.2007.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

The methodological nettle: ICT and student achievement

Abstract: A major challenge for researchers and educators has been to discern the effect of ICT use on student learning outcomes. This paper maps the achievements in Year 10 Science of two cohorts of students over two years where students in the first year studied in a traditional environment while students in the second took part in a blended or e-learning environment. Using both quantitative and qualitative methods, the authors have shown that ICT, through an e-learning intervention, did improve student performance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 4 publications
3
33
0
6
Order By: Relevance
“…Some researchers also claim that ICT can have a positive impact of student attitudes and their learning outcomes (e.g. Chandra and Lloyd 2008 ;Chandra and Briskey 2012 ;Chandra and Watters 2012 ). Hattie ( 2009 ), in his book titled "Visible Learning", investigated more than 800 meta-analyses that were conducted over a 15-year period.…”
Section: Ict In Educationmentioning
confidence: 97%
“…Some researchers also claim that ICT can have a positive impact of student attitudes and their learning outcomes (e.g. Chandra and Lloyd 2008 ;Chandra and Briskey 2012 ;Chandra and Watters 2012 ). Hattie ( 2009 ), in his book titled "Visible Learning", investigated more than 800 meta-analyses that were conducted over a 15-year period.…”
Section: Ict In Educationmentioning
confidence: 97%
“…Mega reviews of research studies in this area unanimously advocate the potential benefits of incorporating ICT in the learning process [9], [10], [11], [12], [13]. The gains achieved through the integration of ICT in the educational process are undeniable: great strides have been made towards taming the technology to meet the emerging demands for education [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a highly modern and technology-focused nation like Singapore, one can assume that these statistics would likely exceed the attributes of US numbers. Research has shown that integrating technology in teaching and learning can have positive influences on students' motivation, inquiry-based learning, attitudes, achievement, and peer interactions in the classrooms (Chandra & Lloyd, 2008;Lim & Tay, 2003;Schofield, 1995;Wang, Kinzie, McGuire, & Pan, 2010).…”
Section: Introductionmentioning
confidence: 99%